International Law and the Peaceful Settlement of Disputes - Fatema Miah (The International Journal of Law Review and State Administration, 2026)
The International Court of Justice (ICJ), established in 1945 as the principal judicial organ of the United Nations (UN), embodies a post World War II commitment to fostering international peace and security through judicial means. Anchored in the UN Charter, it obliges member states to resolve disputes peacefully, building on precedents like the League of Nations while addressing enforcement challenges. Promulgated in 1945 to rectify the League & # 39; s deficiencies, the UN Charter prioritizes preventing global conflicts through structures for peaceful adjudication. International law provides a framework for dispute resolution via treaties, courts, and organizations, mitigating escalations that threaten the peace. This paper examines the evolution, efficacy, and limitations of international law in promoting global dispute resolution. Theoretical Basis and Research Methods Theoretical basis: Explored the variables of international law to explain its role in dispute resolution. Research method: Documentary analysis of sources, journals, and deductive reasoning.